Hospital Costs and Competition for Services: A Multiproduct Analysis - Fournier, Gary M.; Mitchell, Jean M. (The Review of Economics and Statistics, 1992)
The authors estimate the effects of market structure on hospital costs using a translog multiproduct cost function. Recognizing the multiplicity of services provided by hospitals, the results show that costs are substantially determined by service configuration, and that there are distinct economies of size and sco pe. The model also distinguishes market concentration measures by servic e type, including obstetrics, radiation therapy, diagnostic imaging, a nd surgery. Estimates show that, after controlling for the other determinants of cost, the degree of competition has only modest cost-increasing effects. Copyright 1992 by MIT Press.